Three-dimensional mapping of the creatine kinase enzyme reaction rate in muscles of the lower leg - Parasoglou, Prodromos; Xia, Ding; Chang, Gregory; Convit, Antonio; Regatte, Ravinder R. (NMR in biomedicine, 2013)
Phosphorus (31P) magnetization transfer (MT) techniques enable the non‐invasive measurement of metabolic turnover rates of important enzyme‐catalyzed reactions, such as the creatine kinase reaction (CK), a major transducing reaction involving adenosine triphosphate and phosphocreatine. Alteration in the kinetics of the CK reaction rate appears to play a central role in many disease states. In this study, we developed and implemented at ultra‐high field (7T) a novel three‐dimensional 31P‐MT imaging sequence that maps the kinetics of CK in the entire volume of the lower leg at relatively high resolution (0.52 mL voxel size), and within acquisition times that can be tolerated by patients (below 60 min). We tested the sequence on five healthy and two clinically diagnosed type 2 diabetic subjects. Overall, we obtained measurements that are in close agreement with measurements reported previously using spectroscopic methods. Importantly, our spatially resolved method allowed us to measure local CK reaction rate constants and metabolic fluxes in individual muscles in a non‐invasive manner. Furthermore, it allowed us to detect variations of the CK rates of different muscles, which would not have been possible using unlocalized MRS methods. The results of this work suggest that 3D mapping of the CK reaction rates and metabolic fluxes can be achieved in the skeletal muscle in vivo at relatively high spatial resolution and with acquisition times well tolerated by patients. The ability to measure bioenergetics simultaneously in large areas of muscles will bring new insights into possible heterogeneous patterns of muscle metabolism associated with several diseases and serve as a valuable tool for monitoring the efficacy of interventions. Copyright © 2013 John Wiley & Sons, Ltd. In this study, we developed and implemented a novel three‐dimensional 31P‐MT imaging sequence that maps the kinetics of CK in the entire volume of the lower leg within acquisition times that can be tolerated by patients. We tested the sequence on five healthy and two clinically diagnosed type 2 diabetic subjects. Overall, we obtained measurements that are in close agreement with measurements reported previously using spectroscopic methods. Importantly, our spatially resolved method allowed us, in the case of diabetic patients, to detect variations of the CK rate of different calf muscles, which would not have been possible using unlocalized MRS methods.